2009
DOI: 10.1021/jf8029176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cellulase Treatment on Extraction of Antioxidant Phenols from Black Currant (Ribes nigrum L.) Pomace

Abstract: The effect of a commercial cellulase preparation on phenol liberation and extraction from black currant pomace was studied. The enzyme used, which was from Trichoderma spp., was an effective "cellulase-hemicellulase" blend with low β-glucosidase activity and various side activities. Enzyme treatment significantly increased plant cell wall polysaccharide degradation as well as increasing the availability of phenols for subsequent methanolic extraction. The release of anthocyanins and other phenols was dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 38 publications
7
37
0
4
Order By: Relevance
“…Landbo and Meyer (2001) reported that the incorporation of enzymes into the extraction process from blackcurrant juice residues promotes the polyphenols and anthocyanins recovery. A similar result was observed by Kapasakalidis et al (2009), using a commercial cellulose enzyme on blackcurrant pomace.…”
Section: Introductionsupporting
confidence: 86%
“…Landbo and Meyer (2001) reported that the incorporation of enzymes into the extraction process from blackcurrant juice residues promotes the polyphenols and anthocyanins recovery. A similar result was observed by Kapasakalidis et al (2009), using a commercial cellulose enzyme on blackcurrant pomace.…”
Section: Introductionsupporting
confidence: 86%
“…Enzymes also increase the yield of various phenolic compounds in 0308-8146/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved. doi:10.1016/j.foodchem.2011.06.048 the juice (Bagger-Jørgensen & Meyer, 2004;Buchert et al, 2005;Kapasakalidis, Rastall, & Gordon, 2009;Koponen, Buchert, Poutanen, & Törrönen, 2008;Landbo & Meyer, 2001;Landbo & Meyer, 2004). The antimicrobial properties of berry juices have also been reported to increase with enzymatic treatments (Puupponen-Pimiä, Nohynek, Ammann, Oksman-Caldentey, .…”
Section: Introductionmentioning
confidence: 99%
“…Similar increases in anthocyanin and flavonol yields during the production of bilberry juice [27,37], elderberry juice [43] and black currant juice [42] and concentrate [45] were reported previously, when various polygalacturonases and pectin lyases above dosages used in industrial production were applied. Cellulases were reported to enhance cell wall degradation of black currant pomace, thereby facilitating the release of anthocyanins [46]. Yet, there are reports about decreased anthocyanin contents during blueberry [14,47], lingonberry [13] and black currant [44] juice processing.…”
Section: Effect Of Enzyme-assisted Processing Of Bilberries On Juice mentioning
confidence: 99%